Work-related stress and performance among primary school teachers - Sandra Ingried Asaloei; Agustinus Kia Wolomasi; Basilius Redan Werang (International Journal of Evaluation and Research in Education (IJERE), 2020)
Stress influences teachers’ performance and school effectiveness alike. The main objective of this study is to describe work-related stress and its eventual relationship with job performance of teachers working in primary schools of Boven Digoel district, Indonesia. To attain this objective, a survey study was employed by utilizing two survey questionnaires. Research data derived from a total of 352 primary school teachers who were incidentally established as samples. Data were statistically analyzed using Pearson’s correlation analysis. Result of data analysis shows a significant negative correlation between the work-related stress and job performance of teachers working in the primary schools of Boven Digoel district.